Anti‐αIIbβ3 immunization in Glanzmann thrombasthenia: review of literature and treatment recommendations. (2nd April 2018) - Fiore, Mathieu; d'Oiron, Roseline; Pillois, Xavier; Alessi, Marie‐Christine
Summary: Glanzmann thrombasthenia (GT) is caused by inherited defects of the αII b β3 platelet glycoprotein. This bleeding disorder can be treated with platelet transfusion therapy, but some patients will be immunized and begin to form anti‐human leucocyte antigen (HLA) and/or anti‐αII b β3 antibodies. These antibodies can bind and interfere with the function of the transfused platelets, rendering treatment ineffective. However, platelet transfusion refractoriness attributable to HLA antibodies may be managed by the selection of compatible donors, although they are not always readily available, particularly in an emergency. Thus, anti‐αII b β3 antibodies represent one of the most severe complications in GT. Both genetic and environmental factors may contribute to the risk of anti‐αII b β3 development, but the underlying pathogenic mechanisms are still unknown. This review will summarize the current knowledge of the risk factors for development of anti‐αII b β3 antibodies in patients with GT and discuss how these findings may influence the clinical management of patients.